Modeling and simulation of a grid-connected photovoltaic system - Yero, R. Proenza; Camejo, J. Emilio; Heredia, R. Ramos (IJRDO - Journal of Electrical And Electronics Engineering, 2019)
The simulation of a Grid Connected Photovoltaic System (GCPVS) is presented, starting from mathematical models, both for the photovoltaic generator (GPV) and the Photovoltaic Inverter (IPV) of grid connection. MATLAB 2015a software was used as a tool for calculating and processing the equations that define the behavior of the system and allowed, from a database of operation of a GCPVS installed in the Solar Energy Research Center (SERC), rated power 7.5 kWp, validate the model by statistical coefficients.